2012
DOI: 10.1021/nn305065u
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Spinel Phase in the Layered Composite Cathode Used in Li-Ion Batteries

Abstract: Pristine Li-rich layered cathodes, such as Li(1.2)Ni(0.2)Mn(0.6)O(2) and Li(1.2)Ni(0.1)Mn(0.525)Co(0.175)O(2), were identified to exist in two different structures: LiMO(2)R3[overline]m and Li(2)MO(3)C2/m phases. Upon 300 cycles of charge/discharge, both phases gradually transform to the spinel structure. The transition from LiMO(2)R3[overline]m to spinel is accomplished through the migration of transition metal ions to the Li site without breaking down the lattice, leading to the formation of mosaic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
726
1
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 812 publications
(778 citation statements)
references
References 34 publications
24
726
1
7
Order By: Relevance
“…12 and LiFePO 4 that has an olivine-type structure. 13 Although NCA provides a slightly higher practical capacity (160-180 mAh/g) than LiCoO 2 , its thermal instability on delithiation due to the presence of the high valence Ni compromises the safety of Li-ion cells.…”
Section: Rechargeable Li-ion Batteriesmentioning
confidence: 99%
“…12 and LiFePO 4 that has an olivine-type structure. 13 Although NCA provides a slightly higher practical capacity (160-180 mAh/g) than LiCoO 2 , its thermal instability on delithiation due to the presence of the high valence Ni compromises the safety of Li-ion cells.…”
Section: Rechargeable Li-ion Batteriesmentioning
confidence: 99%
“…Due to the structural and chemical complexities of these layered structures, their fading mechanisms have not been fully resolved. Electron microscopy studies indicated that, in lithium and manganese-rich materials, the capacity fading and voltage decay were partially attributed to structural reconstruction inducing a transition from the layered structure to spinel and/or rock-salt structures at the surface and/or in the bulk 5,17,25,26 . A recent study investigated the atomic structure of Li 2 MnO 3 after partial delithiation and re-lithiation to enable improved understanding of lithium-rich/ manganese-rich materials 27 .…”
mentioning
confidence: 99%
“…19,22,23 However, to obtain such a capacity, these materials must be cycled over a wide potential range of 2.5-4.6 V (vs. Li + /Li), which may be challenging for the current carbonate-based electrolytes. Major issues such as large irreversible capacity (IRC), 19,33,34 voltage fade upon cycling 22,[35][36][37][38][39][40] and poor rate capability 22,41,42 have hindered the application of these materials. * Electrochemical Society Student Member.…”
mentioning
confidence: 99%